The Influence Of Implementing A Reward And Punishment System On Employee Work Motivation: A Case Study At PT XYZ Smelter Mineral And Metal Company - Allo, Marsianus Ramba; Saputra, Bobby Wiryawan (Indonesian Journal of Multidisciplinary Science, 2025)
his study examines the influence of implementing a reward and punishment system on employee work motivation at PT XYZ, a mineral and metal smelter company located in South Halmahera Regency, North Maluku Province. The research uses a quantitative approach involving 255 respondents selected through stratified and systematic sampling from a population of 4,245 employees. Data were collected through questionnaires and analyzed using SPSS. The results indicate that both reward and punishment significantly affect work motivation, with reward showing a stronger statistical influence. Reward mechanisms such as performance bonuses and recognition enhance employee engagement, while punishment, applied proportionally through warnings or sanctions, helps maintain discipline. Regression analysis reveals that the combined implementation of reward and punishment explains 37.8% of the variance in work motivation. These findings support Herzberg's Two-Factor Theory, suggesting that reward acts as a primary motivator, while punishment serves as a hygienic factor to prevent dissatisfaction. This study highlights the strategic role of a balanced reward and punishment system in shaping productive employee behavior and offers practical insights for similar industrial organizations seeking to enhance workforce motivation and performance.